Protection of Banteng Home-range within the Protection Areas Sistem Gaps in the Banyuwangi Regency - East Java Province - Muchammad Taufik Tri Hermawan; Muhammad Baiquni; Muhammad Ali Imron (Jurnal Ilmu Kehutanan)
Protected areas hold an important role in biodiversity protection. However, various biodiversity are still unprotected in the existing protected areas system. This paper explains the protected areas system gap for banteng (Bos javanicus) home range in the south area of Banyuwangi district and options of its fulfillment. This research was done in area between Meru Betiri National Park and Alas Purwo National Park, Banyuwangi District, East Java. Study was done using gap analysis, developed by Scott et al. (1987). Banteng home range area was mapped and overlayed with protected area distribution using ArcGis 10.1. Public policy and market mechanism related to area protection and biodiversity was reviewed to perceive opportunity to protect banteng home range areas outside of existing protected areas. Banteng home range also consisted area outside Alas Purwo National Park and Meru Betiri National Park. Evidence of banteng presence could be seen in KPH Banyuwangi Selatan concession and settlement area. In Banyuwangi district spatial plan of 2012-2032 protection areas allocation is advanced from the protected areas, but are still not enough to protect banteng homerange. The HCVF scheme based on market mechanism are more potential to protect banteng home range in areas between Alas Purwo National Park and Meru Betiri National Park.